The Effect of PBL Learning Model and Quizizz Paper Mode on the Learning Outcomes of Students in Social Studies Class IV - Okta Pramudita; Akhmad Junaedi (JURNAL PENDIDIKAN IPS, 2025)
This study was conducted to identify the impact of the Problem Based Learning model an Quizizz Paper Mode media on the learning outcomes of fourth grade elementary school students in social studies subject matter. The background of this research is the need for innovative approaches that can enhance students’ active participation and improve their learning outcomes. The research employed a quantitative approach with a quasi-experimental design involving two classes that received different treatments. A total of 46 respondents participated in the study, consisting of fourth grade elementary school students. Pretest dan posttest were used as research instruments, with data analysis including normality test, homogeneity test, and the Mann-Whitney test. The findings revealed a significant difference between the experimental and control classes (Sig. value 0.000 < 0.05), indicating that the applied learning model and media had a positive effect on Quizizz Paper Mode into social studies learning, which has not been widely examined previously, particularly at the elementary school level. This study recommends the implementation of instructional strategies that align with students’ characteristics and the use of interactive media to support a more effective learning process.